THE IDENTIFICATION OF INDIGENOUS KNOWLEDGE IN KUTAI KARTANEGARA AS SOCIAL STUDIES LEARNING RESOURCE BASED ON GREEN ECONOMY - Reza Reza; Vitria Rahayu; Christie Stephanie Piar (Educational Studies: Conference Series, 2021)
This research aimed to identify the forms of indigenous knowledge and the use of indigenous knowledge (indigenous knowledge) in Kutai as a learning resource-based IPS green economy. The study was conducted using qualitative descriptive data analysis. The object of the research is to find junior high social studies teachers in Kutai who teach as many as 10 people. Collecting data using triangulation techniques which combine several research techniques together, namely: a) observation field (b) documentation (c) unstructured interviews (d) literature and (e) Focused Group Discussion (FGD). The results showed Kutai Kartanegara had various forms of indigenous knowledge which influenced their culture and were relevant to the concept of the Green Economy. Religion and beliefs are classified as 1) knowledge systems, 2) knowledge systems, 3) livelihood systems, 4) attitudes, 5) traditional technology, and 6) arts.The utilization of indigenous knowledge through social studies learning with a contextual approach has an important role in the implementation of the green economy concept.